دراسة الخطاب الإعلامي في ضوء مقاربات اللسانيات النصية - مأمون, محمد إسلام; زياد, إسماعيل (جامعة الوادي - University of Eloued, 2021)
يهدف هذا المقال إلى استعراض مفاهيم وأليات وأهم مقاربات اللسانيات النصية لكل من "روبرت دي بوجراند"، "دريسلر"،"هاليداي"،"رقية حسن"، "تون فان ديك"، و"بروان ويول"، من أدوات واجراءات منهجية في تحليل الخطابات المتنوعة، والتي يمكن تطبيقها في تحليل الخطاب الإعلامي، بوصف اللسانيات النصية فرع لساني جديد يهتم بدراسة النص من حيث كونه الوحدة اللغوية الكبرى، وبالتالي قراءة الخطاب الإعلامي قراءة واحدة كلية غير مجزئة. Abstract: This article aims to reviewing the concepts mechanisms and most important textual linguisticsapproaches of Robert de Beaugrand and Dressler Halliday and Warakia Hassan, Ton Van Dyck, and Braun Woolle from tools and methodological procedures in discourse analysis, which can be applied In media discourse analysis, as textual linguistics is a new linguistic branch;which is concerned with the study of the text in terms of being the major linguistic unit, and thus, reading the media discourse as one undivided total reading.
Studying media discourse in the light of textual linguistics approaches
مقال
Keywords: الخطاب الإعلامي ، مقاربات ، اللسانيات النصية ، النص; Media discourse, approaches, textual linguistics, text.